Active drag related to velocity in male and female swimmers - Toussaint, H. M.; Groot, G. de; Savelberg, H. H. C. M.; Vervoorn, K.; Hollander, A. P.; van Ingen Schenau, G. J. (Journal of Biomechanics, 1988)
Propulsive arm forces of 32 male and 9 female swimmers were measured during front crawl swimming using arms only, in a velocity range between 1.0 m/s and 1.8 m/s. At constant velocity, the measured mean propulsive force Fp equals the mean active drag force (Fp). It was found, that Fd is related to the swimming velocity v, raised to the power 2.12 + 0.20 (males) or 2.28 + 0.35 (females). Although many subjects showed rather constant values of F/v<, 12 subjects gave significantly (p<0.01) stronger or weaker quadratic relationships. Differences in drag force and coefficient of drag between males and females (drag: 28.9 + 5.1 N, 20.4 + 1.9 N, drag coefficient: 0.64 + 0.09, 0.54 + 0.07 respectively) are especially apparent at the lowest swimming velocity (1 m/s), which differences become less at higher swimming velocities. Possible explanations for the power of the velocity from the ideal quadratic dependency are discussed.